The Effectiveness of Reading Culture in Increasing Public Interest in Reading at the Pematangsiantar City Archives and Library Service - Hartati, Sukma; Fathurrahman, Muslih (Inkunabula: Journal of Library Science and Islamic Information, 2025)
Reading interest is a crucial factor in the development of literate human resources. However, a low reading habit remains a persistent issue, including in Pematangsiantar City. In response, the Pematangsiantar City Archives and Library Office implemented the Reading Culture Development Program to enhance public literacy awareness through activities such as mobile library services, reading culture campaigns, and literacy competitions. This study aims to analyze the effectiveness of these activities in increasing public reading interest, identify challenges encountered during implementation, and propose strategies for future development. A qualitative, descriptive design was employed. Data were collected through in-depth interviews with three key informants involved in program implementation and analyzed using Miles and Huberman's interactive model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the program has significantly influenced reading behavior, increased library visits, and fostered literacy habits among students. Despite technical barriers such as limited facilities and time constraints, the program was effectively executed through strong coordination and adaptive delivery strategies. In conclusion, the Reading Culture Development Program has proven effective in cultivating a reading culture. It holds potential as a replicable model for other regions through strategic, theory-based, and community-participatory approaches. Abstrak Minat baca merupakan faktor krusial dalam pembangunan sumber daya manusia yang literat. Namun, rendahnya kebiasaan membaca masih menjadi permasalahan klasik, termasuk di Kota Pematangsiantar. Merespons hal tersebut, Dinas Arsip dan Perpustakaan Kota Pematangsiantar melaksanakan kegiatan Pembudayaan Gemar Membaca untuk meningkatkan kesadaran literasi masyarakat melalui kegiatan Perpustakaan Keliling, Sosialisasi Budaya Membaca, dan Lomba Literasi. Penelitian ini bertujuan untuk menganalisis efektivitas kegiatan tersebut dalam meningkatkan minat baca masyarakat, mengidentifikasi kendala pelaksanaan, serta merumuskan strategi pengembangan ke depan. Metode yang digunakan adalah pendekatan kualitatif dengan desain deskriptif. Data dikumpulkan melalui wawancara mendalam pada tiga informan dengan pihak pelaksana kegiatan dan dianalisis menggunakan teknik analisis interaktif Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kegiatan ini memberikan dampak signifikan terhadap perubahan perilaku membaca, peningkatan kunjungan ke perpustakaan, dan terbentuknya kebiasaan literasi di kalangan pelajar. Meski terdapat hambatan teknis seperti keterbatasan fasilitas dan waktu, kegiatan tetap terlaksana secara efektif berkat koordinasi dan strategi penyampaian yang adaptif. Kesimpulannya, kegiatan Pembudayaan Gemar Membaca terbukti efektif dalam membangun budaya membaca, serta dapat menjadi model yang layak diterapkan di daerah lain dengan pendekatan strategis berbasis teori dan partisipasi komunitas